Penerapan Maqashid Syariah Index pada Perbankan Syariah di Indonesia - Kristianingsih Kristianingsih; R. Abidzar Al Fahri; Fiqi Fahri Al Malik (Journal of Applied Islamic Economics and Finance, 2021)
This study aims to analyze the performance of Islamic banking in Indonesia (case studies in ) using the Maqashid Syariah Index (MSI) approach. This is a quantitative research with descriptive study approach with object of research being12 Islamic commercial banks, 4 banks in Indonesia as Bank Sharia BNI, Sharia BRI, Sharia Mandiri and Sharia BJB. The results showed that the performance of Islamic banking in Indonesia is considered better in the achievement of maqashid sharia.. The measurement results of the Maqasid Syariah Index show the highest ranking of Islamic banking in Indonesia is ranked 1st achieved by Bank Negara Indonesia Syariah with number 0.19138, the second ranking of Islamic banking in Indonesia is achieved by Bank BRI Syariah (BRIS) with 0.14879 and the three ranking of Islamic banking in Indonesian Bank Syariah Mandiri (BSM) was with 0.14580.